Acesso à política de assistência estudantil: uma análise do impacto do auxílio moradia nas trajetórias de estudantes da UFC no Campus Sobral - Nunes, Ilanna Teixeira (2021)
The transformations that higher education has undergone in the last two decades - the expansion process of the university system and the construction of advanced campuses in small and medium-sized cities - has considerably increased the demand for student assistance due to the existence of many young people who find it difficult to move. up to the headquarters of their courses. In this sense, it is considered that the Housing Assistance Program occupies a strategic position in the academic path of many students who live in the northern region of Ceará and questioning what meanings and representations are built about the Program is fundamental. Thus, taking Housing Assistance as the axis of analysis of the experiences of young people in accessing the student assistance policy, some questions guided the research: What is the impact of this Program on the academic trajectories of these subjects? What motivated them to join? If the benefit were suspended by the University, what would be the repercussions on your academic life? The purpose of this research was to understand the perspectives of students from the UFC Campus in Sobral regarding the impact of the Housing Assistance Program in their academic trajectories. It also sought to reconstruct the Program's history, a strategy that seems fundamental to understanding its configurations and ways of operating. The research is of an applied nature, with a qualitative focus. From the point of view of its objectives, it is a descriptive investigation. The procedures for data collection used were documentary, bibliographic and field. In the dialogue with the study participants, eight interviews were carried out, with semi-structured question scripts. Another relevant source of data for the construction of the work is the socioeconomic information of the students collected with the Student Assistance Team of the Campus. The theoretical discussion has been carried out based on the works of several scholars who carried out investigations on higher education in popular circles, emphasizing formulations within the scope of the sociology of education. This research will enable contributions in the practical field of student assistance policy at the University as it subsidizes the interventions of professionals working in this area, in particular the servers of the Campus de Sobral, in addition to the production of studies and content on the subject.